VICTIM TURNED PERPETRATOR: THE TRANSFORMATION OF VICTIMIZATION EXPERIENCES INTO CRIMINAL BEHAVIOR - Kurnia Mega Tulung; Adrianus Eliasta Meliala (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The phenomenon of victims transforming into perpetrators (Victim-Offender Overlap) in Indonesia is a phenomenon that is still developing. This study employs a qualitative approach to explore the process of transformation from victimization experiences to criminal behaviors, focusing on those with a history of victimization. Data collection involved purposive sampling and semi-structured interviews to gain in-depth insights into the victims' experiences and transformation processes of the informants. The findings of this study have proven to support and even complement the results of previous studies related to the transformation caused by post-victimization experience, namely, Adverse Childhood Experiences (ACE's), Other Forms of Victimization Experiences, and Other Adverse Experiences. These findings suggest that the transformation process is not only triggered by victimization in adulthood, so it is important to further explore the relationship between victimization and criminal behavior in a broader context.